Predicting Psychological Well-being of the Elderly Based on Cognitive Impairment and Negative Emotions Mediated by Coping Self-efficacy and Social Support - Azam Mohammadi; Mohammad Hossein Abdollahi; Robabe Noury; Hadi Hashemi Razini; Mahnaz Shahgholian (University of Social Welfare & Rehabilitation Sciences, 2023)
Objectives: This study aim to investigate whether psychological well-being of the elderly can be predicted by cognitive impairment and negative emotions mediated by coping self-efficacy and social support. Methods & Materials: This is a correlational study using structural equation modeling (SEM). Participants were 450 older adults, including 247 men (54.9%) and 203 women (45.1%), aged 60-80 years in Tehran, Iran who were selected by a convenience sampling method based on the entry and exit criteria. The demographic variables (age, marital status, number of children, education level and income level) and the history of physical diseases were recorded. The research tools included Ryff's psychological well-being scale, Positive and Negative Affect Scale, Mini-Mental State Examination, Coping Self-Efficacy Scale, and Social Provisions Scale. Fitness of the study model was estimated using SEM in LISREL software. The mediating relationships in the proposed model was tested using the bootstrap procedure. Results: The Mean±SD age of male participants was 66.34±5.34 years and the mean age of female participants was 65.57±6.08 years. The results showed that the proposed model had good fit. The four indirect pathways were statistically significant. Cognitive impairment with standard coefficients of -0.57, -0.60, and -0.27 had an impact on social support, coping self-efficacy, and psychological well-being, respectively. Negative emotions also had an effect on social support, coping self-efficacy and psychological well-being with coefficients of -0.28, -0.34 and -0.11, respectively. The effect of coping self-efficacy on psychological well-being had a standard coefficient of 0.15, and the effect of social support on psychological well-being had a standard coefficient of 0.57. Conclusion: These findings highlight the importance of coping self-efficacy and social support in improvement of psychological well-being and consequently prevention of adverse outcomes due to cognitive impairment in the elderly. It is recommended to develop comprehensive and practical strategies to strengthen the internal and external resources of older people and improve their health.